Early Paleocene Paleoceanography and Export Productivity in the Chicxulub Crater. Issue 11 (30th October 2021) - Lowery, Christopher M.; Jones, Heather L.; Bralower, Timothy J.; Cruz, Ligia Perez; Gebhardt, Catalina; Whalen, Michael T.; Chenot, Elise; Smit, Jan; Phillips, Marcie Purkey; Choumiline, Konstantin; Arenillas, Ignacio; Arz, Jose A.; et al.
Abstract: The Chicxulub impact caused a crash in productivity in the world's oceans which contributed to the extinction of ∼75% of marine species. In the immediate aftermath of the extinction, export productivity was locally highly variable, with some sites, including the Chicxulub crater, recording elevated export production. The long‐term transition back to more stable export productivity regimes has been poorly documented. Here, we present elemental abundances, foraminifer and calcareous nannoplankton assemblage counts, total organic carbon, and bulk carbonate carbon isotope data from the Chicxulub crater to reconstruct changes in export productivity during the first 3 Myr of the Paleocene. We show that export production was elevated for the first 320 kyr of the Paleocene, declined from 320 kyr to 1.2 Myr, and then remained low thereafter. A key interval in this long decline occurred 900 kyr to 1.2 Myr post impact, as calcareous nannoplankton assemblages began to diversify. This interval is associated with fluctuations in water column stratification and terrigenous flux, but these variables are uncorrelated to export productivity. Instead, we postulate that the turnover in the phytoplankton community from a post‐extinction assemblage dominated by picoplankton (which promoted nutrient recycling in the euphotic zone) to a Paleocene pelagic community dominated by relatively larger primary producers like calcareous nannoplankton (which more efficiently removed nutrients from surface waters, leading to oligotrophy) is responsible for the decline in export production in the southern Gulf of Mexico. Plain Language Summary: The end Cretaceous mass extinction was caused by the impact of an asteroid in what is now the Yucatán Peninsula, México. The impact ejected aerosols and dust into the air that reduced sunlight transmission, causing a severe decline in photosynthesis and the collapse of marine food webs. However, the change in the amount of organic matter created by photosynthesizing plankton that was delivered to the seafloor (export productivity) was variable across the oceans. At some places, including the Chicxulub crater, export productivity was actually high immediately after the impact. We produced a ∼3‐million ‐year record of export productivity in the crater to determine how long it remained elevated and why it eventually declined. Export production was very high for the first 320, 000 years after the impact, declined from 320, 000 to 1, 200, 000 years after the impact, and then remained low. We found that this production was not related to the input of nutrients nor the degree of stratification of the ocean, but instead was probably driven by the increase in the cell size of phytoplankton. Larger phytoplankton removed nutrients from the surface waters as they sank, prompting an increase in species which are better adapted to low‐nutrient waters. Key Points: Export productivity at Chicxulub was elevated for 1.2 Myr post K‐Pg; it was very high for the first 0.32 Myr and declined from 0.32–1.2 Myr The final decline in export productivity ∼0.9–1.2 Myr is associated with the termination of calcareous nannoplankton disaster assemblages Export productivity change is not correlated with stratification or terrigenous input and was likely driven by changes in the phytoplankton